Vascular synovial phenotype indicates poor response to JAK inhibitors in rheumatoid arthritis patients: a pilot study - Liu,Mengxia; Liu,Pengcheng; Li,JianBin; Huang,Yiping; Wu,Rui (PeerJ, 2024)
Objective Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease, characterized by significant individual variations in treatment response. Predicting treatment response remains a formidable challenge. This study aims to identify predictors within the synovium associated with the response to JAK inhibitor therapy in RA patients, employing a retrospective approach. Methods A retrospective analysis was conducted on 27 RA patients who underwent synovial biopsy and received JAK inhibitor therapy for at least three months at our center, from January to November 2023. These patients had comprehensive clinical records. Based on their response to JAK inhibitor therapy, as measured by the ACR20 criteria, they were categorized into non-responder and responder groups. We compared clinical data (including sex, age, disease duration), laboratory findings (RF, ACPA, ESR, CRP, etc.), DAS28-CRP scores, and synovial pathology features—such as synovial lining hyperplasia, neovascularization, stromal activation, inflammatory infiltration, and the expression of CD3, CD20, CD68, and CD138 markers in the synovium—between the two groups. Results The rate of non-responder to JAKi was found to be 33.3% (nine cases out of a total of 27 patients). Non-responders, when compared to responders, exhibited longer disease duration, more pronounced synovial neovascularization alongside reduced infiltration of labeled CD20+ and CD138+ cells in the synovium. Multivariate regression analysis identified synovial neovascularization and disease duration as independent predictors of a poor response to JAK inhibitor treatment. Conclusions The presence of vascular phenotype with low inflammation within the synovium of RA patients is an indicator of poor response to JAK inhibitor therapy, highlighting its potential as a predictive marker for treatment outcomes.
Keywords: Rheumatoid arthritis; Synovial biopsy; JAK inhibitors; Treatment response